The antidepressant and anxiolytic effect of GPER on translocator protein (TSPO) via protein kinase a (PKA) signaling in menopausal female rats. Issue 207 (March 2021) - Wang, Jing; Li, Hao-Yuan; Shen, Shi-Yu; Zhang, Jia-Rui; Liang, Ling-Feng; Huang, Hui-Jie; Li, Bing; Wu, Gen-Cheng; Zhang, Yu-Qiu; Yu, Jin
Highlights: Suppression or genetic deletion of GPER could induce depressive or anxiety-like symptoms in female animals. Intracerebroventricularly activation GPER by G-1 exhibited antidepressant and anxiolytic-like effects in OVX female rats. G-1 alleviated hippocampal redox status in OVX female rats. G-1 accelerated PKA activation and enhanced TSPO phosphorylation. PKA antagonist PKI partially antagonized the anti-anxiety and anti-depression effects of G-1. Abstract: Postmenopausal depression is mainly caused by the deprivation of ovarian hormones during menopausal transition, it is of great importance to study on the treatment that could effectively relieve symptoms of menopausal depression with fewer side effects. Activation of G-protein-coupled estrogen receptor (GPER) has long been reported to facilitate neuronal plasticity and improve cognition in animals. Meanwhile, it could participate in regulation of intracellular signaling pathways through the characteristic of GPER, ameliorate intracellular mitochondrial function and oxidative stress. However, the impact of GPER on regulating estrogen deprived-depressant and anxious behaviors is still largely unknown. Here we used the ovariectomized female rats to imitate the condition of menopause. Owing to the lateral ventricle administration of G-1 which specifically react with GPER receptor intracerebrally, Ovariectomized (OVX) female rats showed depressive- or anxiety-like phenotypes with attenuated mitochondrial function. In addition, G-1 facilitated PKA activation, which further accelerated TSPO phosphorylation and alleviated menopausal depression- and anxiety-like behaviors. Moreover, PKA inhibitor PKI could partially antagonized the anti-anxiety and anti-depression effects of G-1. Taken together, we concluded that GPER activation might exhibit antidepressant and anxiolytic effect by elevating TSPO phosphorylation via protein kinase A signaling and rescuing the redox status in menopausal female rats.